Development and validation of spectroscopic methods for simultaneous estimation of combination of antibiotic agents - Prerana Sanas; Amol Kulkarni (International Journal of Pharmacy and Analytical Research, 2016)
A simple, sensitive rapid and reproducible UV and method has been developed and validated for simultaneous determination of Cefixime and Pefloxacin in bulk and pharmaceutical formulation. For development of UV method for Cefixime and Pefloxacin methanol was used as solvent and detection wavelength were found to be at 289.0 nm and 232.80 nm respectively. The method was found to linear in concentration range 10 -35 µg/ml for both drugs the precision and repeatability results showed %RSD less than 2%. The LOD was found to be 0.6445µg/ml and 1.7187 µg/ml for CEF and PEF respectively and LOQ was found to be 1.9531 µg/ml and 5.2083 µg/ml for CEF and PEF respectively. The method was validated as per ICH guidelines.